Energy saving proactive neighbor discovery algorithm in mobile low-duty-cycle wireless sensor network - Junbin LIANG; Xiang ZHOU; Taoshen LI (Tongxin xuebao)
Mobile low-duty-cycle wireless sensor network is a new kind of wireless multi-hop network,which is self-organized by a large number of nodes that have mobile ability and are able to get into sleep for a long time.Such networks have wide application prospects in national defense,industry,agriculture and other fields that need long term monitoring in severe environments.However,the movement and the sleeping features of nodes lead to constantly change of network topology,which makes the nodes difficult to discover their neighbors quickly.Therefore,the nodes cannot achieve optimal distribution decisions.In order to solve this problem,a new proactive neighbor discovery algorithm was proposed.This algorithm made the nodes in the network take the initiative to find their neighbors when they woke up,and avoided the delay caused by long time waiting in the traditional passive neighbor discovery.In addition,by predicting the movement speed and distance of neighbors,the neighbor set at the next moment can be quickly determined,which can further reduce the delay and obtain more accurate neighbor discovery results.Theoretical analysis and experimental results show that compared with the existing algorithms,the algorithm can find all the neighbors in MLDC-WSN with less energy consumption and lower delay.